TATA KELOLA REKAM MEDIS BERBASIS TEKNOLOGI INFORMASI DALAM MONITORING KUNJUNGAN PASIEN IGD DENGAN MENGGUNAKAN METODE AGILE - Hartono, Adellia Permatasari; Syahidin, Yuda; Sari, Irda (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
This study aims to simplify and expedite the processing of patient data, as well as the preparation of reports for officers. In addition, it aims to design an information system for emergency room patient visits to process patient data more quickly and effectively. This study employs a qualitative method with a descriptive approach. Data collection techniques include observation, interviews, and supplemented by literature study. The development method follows agile principles. The problems identified in this study are as follows: There is no information system for emergency patient visits, and the patient visit data for emergency departments are still being recorded using Microsoft Excel. With the implementation of this information system, officers can process patient data quickly and easily, as the computerized system is more organized and better integrated than before.